Optimizing the Economic Impact of Increasing Domestic Content through an Interregional Input-Output and Linear Programming Approach: A Case Study of Geothermal Power Plant Investment in the Java-Madura-Bali Region, 2021-2030 - Junaidi; Sonny Harry B. Harmadi (Jurnal Ragam Pengabdian, 2026)
Investment in the expansion of New and Renewable Energy (NRE) power generation is an essential part of the energy transition program as a commitment to controlling global warming. Based on its characteristics, geothermal power plants (GPP) are the most suitable NRE option to replace coal-fired steam power plants. This commitment is reflected in the Indonesian government’s approval of the 2021–2030 Electricity Supply Business Plan (RUPTL) of PT PLN (Persero), which plans the addition of 3.15 GW of geothermal power capacity, with 60.77% located in the Java–Madura–Bali region. However, the domestic content level (Tingkat Komponen Dalam Negeri, TKDN) of geothermal power plant investments remains relatively low, resulting in suboptimal national economic impacts. This study aims to optimize the economic impact of geothermal power plant investment in the Java–Madura–Bali region under combined TKDN enhancement scenarios, using an Interregional Input–Output (IRIO) and Linear Programming approach. The results provide the optimal economic impacts for each scenario as well as target increases in TKDN for each investment cost component. The findings indicate that the initial priority for increasing TKDN in geothermal power plant investment lies in the civil and steel structures cost component